Penerapan Media Permainan Kartu Domino untuk Meningkatkan Minat dan Hasil Belajar Peserta Didik Sekolah Dasar - Lia Atika Wati; Amrullah; Dika Areka (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to improve the interest and learning outcomes of elementary school students by using domino card game media. This study is a Classroom Action Research (CAR). The subjects used in this study were 27 students of Elementary School 12 Mataram Class 3. Data collection techniques used were observation, tests, questionnaires and documentation. Data were analyzed using quantitative descriptive. The results of the study showed an increase in learning interest and learning outcomes of students by implementing domino card game media. This can be seen from the increase in the percentage of student learning interest before the implementation of domino card game media reached 61.4 percent which means in the good category to 87 percent which means in the very good category after receiving the implementation of domino card game media. Learning outcomes also increased with an average cognitive result of 49.9 to 78.5 with an N-Gain of 0.6 which is categorized as medium. Therefore, the implementation of domino card games in elementary schools, especially at SDN 12 Mataram, is one way to improve the quality of education at the school, which is evident in the students' enjoyment, curiosity, and enthusiasm for the learning process. Students experience a fun learning process, which leads to a deeper understanding of the material. Their enthusiasm for completing and correctly answering each question in the domino card game has resulted in improved learning outcomes.